2010
DOI: 10.1104/pp.109.151639
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Efficient Multipurpose Bean Pod Mottle Virus Viral Vector Set for Foreign Gene Expression and RNA Silencing  

Abstract: Plant viral vectors are valuable tools for heterologous gene expression, and because of virus-induced gene silencing (VIGS), they also have important applications as reverse genetics tools for gene function studies. Viral vectors are especially useful for plants such as soybean (Glycine max) that are recalcitrant to transformation. Previously, two generations of bean pod mottle virus (BPMV; genus Comovirus) vectors have been developed for overexpressing and silencing genes in soybean. However, the design of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
182
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(192 citation statements)
references
References 36 publications
(66 reference statements)
1
182
1
Order By: Relevance
“…These results are consistent with those obtained using other viral systems (Constantin et al 2008;Liu and Page 2008;Zhang et al 2010). In addition to the insert size and position of target genes, the effect of the cloning orientation of the foreign gene was investigated using white lupin plants.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results are consistent with those obtained using other viral systems (Constantin et al 2008;Liu and Page 2008;Zhang et al 2010). In addition to the insert size and position of target genes, the effect of the cloning orientation of the foreign gene was investigated using white lupin plants.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to the insert size and position of target genes, the effect of the cloning orientation of the foreign gene was investigated using white lupin plants. No clear differences were detected between sense and antisense orientations in this study (Figure 4), although antisense fragments have been shown to be more effective for silencing in other VIGS systems (Igarashi et al 2009;Pflieger et al 2008;Zhang et al 2010). …”
Section: Discussionmentioning
confidence: 60%
“…2) The epistatic interaction between CBB resistance gene(s)/or QTL would make the application of MMs to assist in breeding CBB resistance bean and the cloning of the QTL more complex, and 3) the recalcitrant nature of common bean to transformation make the validation of CGs coding for CBB resistance more difficult to accomplish. So it is an urgent task for bean researchers to develop novel approaches, such as virus induced gene silencing (VIGS) (Zhang et al, 2010) for validating the functions of CGs in common bean.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…Seeds of soybean (Glycine max 'Williams 82') used in this study were harvested from greenhouse-grown plants previously indexed for the absence of BPMV and SMV (Zhang et al, , 2010. Soybean plants were maintained in a greenhouse or growth chamber at 22°C with a photoperiod of 16 h.…”
Section: Plant Materialsmentioning
confidence: 99%